Pengembangan Aplikasi Risalah Tuntunan Shalat Secara Lengkap Berbasis Android - Wahyuddin, Wahyuddin; As, Kurniawan (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
The majority of Muslims establish prayer, but not a few who do not know the meaning of reading and prayer movements properly. The purpose of this study is to make it easier for people to know the complete guide to prayer based on Android. The data obtained by means of observation and literature study. By using Research and Development (R&D) research methods. This application is made using the JavaScript programming language and React Native., which is divided into two parts, namely admin and user. The main function of the admin is to add and update the minutes of prayer guidance material. While the user can access the latest material that has been inputted by the admin. The results of this study are to review the material about the complete prayer guidance treatise such as prayer, ablution, tayammum, bathing and others equipped with illustrated images, audio and video procedures for doing it, and there are several features such as short suras, Qibla direction, prayer times, and the location of the nearest mosque with the android application.